MiR‐138 plays an important role in diabetic nephropathy through SIRT1–p38–TTP regulatory axis. Issue 9 (12th April 2021) - Liu, Fengxun; Guo, Jia; Qiao, Yingjin; Pan, Shaokang; Duan, Jiayu; Liu, Dongwei; Liu, Zhangsuo
Abstract: Diabetic nephropathy (DN) is the main cause of chronic kidney disease (CKD) and is one of the most common and serious complications of diabetes mellitus (DM). Sirtuin 1 (SIRT1) and tristetraprolin (TTP) are two important protective factors in DN; however, the regulatory relationship between SIRT1 and TTP, and the underneath mechanism are interesting but still unclear. Identifying the key factors that regulate SIRT1 or TTP may be of great value to the understanding and treatment of the DN. In this study, through systematic experimental methods, we found that the expression of miR‐138 was significantly upregulated in DN clinical patient samples, and our experimental results suggested that miR‐138 could bind the 3ʹ‐UTR of SIRT1 and inhibit its expression in both cultured podocytes and db/db mice kidney tissues. Furthermore, our in vitro and in vivo experiments also indicated miR‐138 could target SIRT1 and affect TTP through p38 pathway. And downregulation of miR‐138 attenuated podocyte injury and showed some extent of therapeutic effects in DN mice models. Our findings revealed that the regulatory axis of miR‐138–SIRT1–p38–TTP might play a key role in DN. We believe that these findings may be of some value for deepening the understanding of DN and may serve as a reference for future treatment of this disease. Abstract : The miR‐138/SIRT1/p38/TTP axis can regulate podocyte injury in diabetic nephropathy (DN). Knockdown of miR‐138 in DN model mice could alleviate DN.